A BPM Maturity Model to guide the evolution of BPM Competences in a Public Institution - Vilela, Jéssyka; Alves, Carina (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: Business Process Management (BPM) has proven to be an essential practice for optimizing operational efficiency, especially in public institutions that face complex challenges related to hierarchical rigidity and the implementation of organizational changes. Problem: The lack of BPM maturity models tailored to the public sector creates significant gaps in the ability of government organizations to assess and improve their BPM competencies. Without a clear framework, these institutions struggle to improve their processes and reach higher levels of maturity. Solution: This work proposes a BPM maturity model specifically developed for public institutions, aiming to support the gradual evolution of their process management competencies. The model includes six key factors and 51 capability areas, along with five maturity levels that provide clear guidelines for implementation. IS Theory: The research is based on the Design Science Research (DSR) approach, which guides the development and evaluation of practical artifacts and theoretical contributions. The proposed model aims to contribute to the BPM maturity theory, especially in the public context. Method: The study was conducted through a case study in a Brazilian public institution, where the maturity model was applied to assess the current BPM level. The evaluation was supported by a spreadsheet tool that automates the maturity level verification process. Results: The maturity model evaluation revealed that the public institution studied had not yet reached maturity level two, indicating the need for significant improvements in strategic areas. The assessments highlighted the model’s usefulness as a practical tool for identifying deficiencies and outlining clear action plans. Contributions and Impact: This work contributes to the field of Information Systems (IS) by offering a maturity model adapted to the public sector, providing a practical and prescriptive approach to improving business process management.